작업기억과 단기기억의 요구수준이 언어수행력에 미치는 효과 - 유재연(Jae Yeon Yoo); 임경열(Kyoung Yuel Lim) (언어치료연구, 2015)
배경 및 목적: 심적자원을 평가하는데 주로 사용되는 작업기억은 실행주의력, 단기기억, 처리로 구성되어 있다. 본 연구에서는 작업기억의 구성요소인 단기기억과 언어수행력과의 관련성을 알아보고자 하였다. 본 연구에서는 단기기억과 언어수행력과의 관련성을 살펴보기 알아보는 방법으로 작업기억력과 단기기억력의 요구수준에 따른 언어수행력의 정도를 측정하였다. 방법: 본 연구는 OO광역시에 소재한 OO대학교에 재학 중인 정상성인 60명을 대상으로 하였다. 모든 대상자들의 작업기억을 측정하기 위한 과제로 숫자역순외우기를 실시하였다. 그리고 컴퓨터 토큰 검사를 이용하여 언어수행력과 언어수행 효율성을 평가하였다. 특히, 컴퓨터 토큰 검사는 토큰 수(2단계 지시 따르기 vs 3단계 지시 따르기)를 조절하여 단기기억력 요구정도에 따른 언어수행력을 알아 보았다. 측정한 작업기억 점수를 바탕으로 피험자들을 상위 작업기억을 가진 집단과 하위 작업기억력을 가진 집단으로 분류하였다. 상위 작업기억 집단과 하위 작업기억 집단을 대상으로 단기기억 요구수준에 따른 언어수행력과 언어효율성을 비교하였다. 결과: 첫째, 단기기억 요구수준이 높은 조건에서 상위 작업기억 집단이 하위 작업기억 집단보다 더 높은 언어수행력 점수가 더 높았다(p<.011). 둘째, 단기기억 요구수준이 높은 조건에서 상위 작업기억 집단이 하위작업 집단보다 더 높은 언어효율을 보였다(p<.001). 셋째, 단기기억 요구수준이 낮은 조건에서는 언어수행력과 언어효율성 모두에서 두 집단 간에 유의한 차이가 나타나지 않았다. 논의 및 결론: 본 연구에서는 정상성인의 언어수행에 있어 단기기억의 중요성을 확인할 수 있었다. 특히, 작업기억에서 실행주의력 뿐만 아니라 단기기억이 작업기억과 상호작용한다는 결과를 보여줌으로써 Engle 등(1999)의 작업기억 모델에서 세 구성요소들에 대한 재조명이 필요함을 제시하였다. 또한, 작업기억 모델이 언어수행에 필요한 심적자원과 언어처리과정을 연구하는데 있어 적합한 모델임을 재확인할 수 있었다. Purpose: Working memory to evaluate mental resources consists of executive attention, short-term memory, and processing. This study aimed at investigating the relationship between working memory and short-term memory. In particular, the purpose of this study was to examine the effect of working memory and the level of short-term memory in language performance. Methods: Sixty young normal adults participated in this study. They completed a backward digit span as a working memory test and a computerized token test as a language performance test that had two levels of short-term memory. The subjects were divided into two groups (high and low) by their digit span score; the language performance scores and efficiency score from the computerized token test were compared between the high and low working memory groups. Results: The language performance scores and efficiency score of the group with high working memory were significantly higher than that of the low working memory group in three token conditions. However, there were no differences between the two groups in language performance score and efficiency score in two token sentences. Conclusions: The study suggests that short-term memory is also an important component of working memory that can burden mental resources while people process language with their own mental resources in a state of low burden. That is, short-term memory may also consume mental resources that are the restricted fuel for mental processing of human beings. Future studies need to investigated the relationship among the three components of working memory: executive attention, short-term memory, and processing. KCI Citation Count: 1